Biochemical and histopathological changes in the kidney and adrenal gland of rats following repeated exposure to lambda-cyhalothrin - Hassina Khaldoun Oularbi (MDPI AG, 2014)
Lambda-cyhalothrin (LCT) is a type II pyrethroid insecticide widely used in pest management. This study was undertaken to evaluate the toxic effects of LCT on the kidneys and adrenal glands of rats after subacute exposure. Twenty-eight 6-week-old male albino Rattus norvegicus rats were randomly assigned to four groups. Group 1 was the control group, which received distilled water. The experimental groups 2, 3 and 4 received 20.4, 30.6 and 61.2 mg/kg body weight, respectively, of LCT, administered orally over 28 days. The effects of the insecticide on various biochemical parameters were evaluated at 14 and 28 days. Histopathological studies were carried out in the kidneys and adrenal glands at the end of the experiment. Lambda-cyhalothrin, as a pyrethroid insecticide, induced significant increases (P≤0.05) in plasma urea, creatinine, uric acid and glucose concentrations, and alanine aminotransferase and aspartate aminotransferase activities after 14 and 28 days. In the rat plasma samples after 28 days, residual concentrations of LCT 1R, cis,